MicroRNAs in Neurocognitive and Neuroprotective Outcomes of Bariatric Surgery: Decoding Pathways to Precision Medicine - Meneses Rêgo, Amalia Cinthia; Araújo-Filho, Irami (International Journal of Innovative Research in Medical Science, 2025)
Bariatric surgery has demonstrated significant benefits in reversing obesity-induced cognitive decline and promoting neuroprotection, yet the molecular mechanisms underlying these effects remain poorly understood. Among the critical regulators of these processes are microRNAs (miRNAs), which orchestrate inflammatory, metabolic, and neuroplastic pathways central to systemic and neural recovery. This review aims to synthesize current evidence on the role of miRNAs in mediating the neurocognitive and neuroprotective benefits of bariatric surgery, focusing on their involvement in modulating neuroinflammation, oxidative stress, and synaptic plasticity. A systematic analysis of studies across multiple databases was conducted to explore the impact of bariatric surgery on miRNA expression and its correlation with neurocognitive outcomes. Findings reveal that specific miRNAs, such as miR-122 and miR-92a, play pivotal roles in reducing systemic inflammation and enhancing mitochondrial function, contributing to improved cognitive performance and resilience against neurodegenerative stressors. The potential of miRNAs as biomarkers for predicting surgical outcomes and guiding personalized therapeutic strategies is highlighted, emphasizing their relevance in precision medicine. Despite these advancements, significant gaps remain in understanding long-term miRNA dynamics, their tissue-specific roles, and their interactions with other regulatory RNAs. Research should prioritize multi-omics approaches and longitudinal studies to elucidate these complexities and optimize miRNA-targeted interventions. This review comprehensively overviews the emerging intersection between miRNAs, bariatric surgery, and neurocognitive health. It offers valuable insights for advancing therapeutic strategies and addressing obesity-related neurological complications.